Reminder : 10th ELIA Biennial Conference Gothenburg: Speeches and reflections. - Wainwright, Chris; Delfos, Carla; University of Gothenburg ([S.l.] : European League of Institutes of the Arts, 2009)
Gbadamosi, Raimi ; Barrett, Bill ; Dhupa, Venu ; Burnett, Ron ; Tiller, Chrissie ; Wainwright, Chris ; Sucha, Vladimir ; Sellars,Peter ; Mometti, Sally ; et al.
University of Gothenburg, Gothenburg, june 2009
boek